2013
DOI: 10.1097/01.nnd.0000433150.18384.1c
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Staff Nurse Perceptions of Competency to Care for Patients With Psychiatric or Behavioral Health Concerns

Abstract: Disruptive behaviors are common among hospitalized patients with psychiatric and substance abuse behaviors. Nurses working on nonpsychiatric units, however, may lack competencies to care for patients with such behaviors. A survey was developed and administered to 844 nurses across three hospital settings that revealed a lack of nurse confidence to intervene in situations that require de-escalation techniques and crisis communication. This study provides direction for further research and interventions in hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 29 publications
2
17
0
5
Order By: Relevance
“…정신질환자가 신체질환으로 인해 일반병동에 입원한 경우, 정신과 간호사(psychiatric nurse)의 상대적 개념으로 흔히 사 용되는 일반병동 간호사(non-psychiatric nurse)는 정신질환 자에 대한 과중한 간호부담감을 갖게 된다 [5,9,10]. 간호부담감 이란 만성질환자를 돌보는 사람이 환자의 행동이나 상태변화 를 야기할 수 있는 상황이나 사건과 관련되어 경험하게 되는 어 려움과 불편감을 말한다 [11].…”
unclassified
See 2 more Smart Citations
“…정신질환자가 신체질환으로 인해 일반병동에 입원한 경우, 정신과 간호사(psychiatric nurse)의 상대적 개념으로 흔히 사 용되는 일반병동 간호사(non-psychiatric nurse)는 정신질환 자에 대한 과중한 간호부담감을 갖게 된다 [5,9,10]. 간호부담감 이란 만성질환자를 돌보는 사람이 환자의 행동이나 상태변화 를 야기할 수 있는 상황이나 사건과 관련되어 경험하게 되는 어 려움과 불편감을 말한다 [11].…”
unclassified
“…간호부담감 이란 만성질환자를 돌보는 사람이 환자의 행동이나 상태변화 를 야기할 수 있는 상황이나 사건과 관련되어 경험하게 되는 어 려움과 불편감을 말한다 [11]. 일반병동 간호사의 정신질환자 간호는 신체에 대한 간호업무와 더불어 심리 ․ 행동 문제까지 간호해야 하는 부담감을 갖게 한다 [9]. 특히, 치료적 환경이 구 비되어 있는 정신과 병동과 달리 환자의 정신증적 증상에 대해 대처할 수 있는 환경적 장치가 제한되어 있는 일반병동에서 환 자의 안전을 책임져야 하는 일반병동 간호사의 정신질환자 간 호부담감은 높아질 수밖에 없다 [10].…”
unclassified
See 1 more Smart Citation
“…Tahapan evaluasi masih ada beberapa hal yang berbeda seperti jenis format evaluasi dan cara mengisi. Hasil penelitian (Rutledge et al 2013) menyatakan bahwa perawat jiwa mampu melakukan pengkajian pada pasien dengan gangguan jiwa namun tidak percaya diri dalam memberikan intervensi terkait perawatan pasien.…”
Section: Tema 1 Memberikan Asuhan Keperawatan Jiwaunclassified
“…19 Nurses report feeling poorly prepared to deal with patients with complex needs 20 and to cope with patients who may have multiple social issues and exhibit challenging or disruptive behaviour on the ward. 21 Both staff and YAA patients alike report problems with communication in the acute setting. Studies have found that a signifi cant proportion of doctors feel uncomfortable talking to young people.…”
Section: Yaas and The Amu: Challengesmentioning
confidence: 99%